2017
DOI: 10.1186/s12911-017-0547-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of data quality of interRAI assessments in home and community care

Abstract: BackgroundThe aim of this project is to describe the quality of assessment data regularly collected in home and community, with techniques adapted from an evaluation of the quality of long-term care data in Canada.MethodsData collected using the Resident Assessment Instrument – Home Care (RAI-HC) in Ontario and British Columbia (BC) as well as the interRAI Community Health Assessment (CHA) in Ontario were analyzed using descriptive statistics, Pearson’s r correlation, and Cronbach’s alpha in order to assess tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 29 publications
3
52
0
Order By: Relevance
“…A study of RAI-MDS 2.0 assessments completed in Ontario postacute care hospitals and residential long-term care facilities found that the data that were collected were of high quality 2. Similarly, the quality of the data collected using the Resident Assessment Instrument-Home Care, the counterpart assessment of the RAI-MDS 2.0 for use in home care settings, was also found to be strong 14…”
Section: Introductionmentioning
confidence: 99%
“…A study of RAI-MDS 2.0 assessments completed in Ontario postacute care hospitals and residential long-term care facilities found that the data that were collected were of high quality 2. Similarly, the quality of the data collected using the Resident Assessment Instrument-Home Care, the counterpart assessment of the RAI-MDS 2.0 for use in home care settings, was also found to be strong 14…”
Section: Introductionmentioning
confidence: 99%
“…The DRS uses 7 items from the RAI-HC to construct a scale from 0 to 14, with higher scores representing stronger indication of depressive illness. A cut-point of 3 or greater for the DRS was adopted as evidence of possible depressive illness that is consistent with other studies of this population (Hirdes, Mitchell, Maxwell, & White, 2011;Hogeveen, Chen, & Hirdes, 2017).…”
Section: Introductionmentioning
confidence: 62%
“…To appraise this, interRAI has a long history of engaging in inter-rater reliability testing of its assessment systems (142,143,191,(241)(242)(243)(244)(245)(246)(247)(248). The approach used has been to conduct independent assessments of service recipients without contact between the assessors and with a limited time gap between assessments.…”
Section: Reliability Inter-rater Reliabilitymentioning
confidence: 99%
“…The patterns of associations in a dataset can provide insights about whether the instrument measures what one thinks it measures. The initial version of the MH was successfully evaluated by examining the presence of expected associations with age of cognitive loss and functional decline, the relationship between depression measures in suicide related indicators, readmission rates and problems with medication management, and cognitive performance with behavior (248).…”
Section: Convergent Validitymentioning
confidence: 99%